2018
DOI: 10.1111/1755-0998.12910
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatic pipeline for identifying informative SNP panels for parentage assignment from RADseq data

Abstract: The development of high-throughput sequencing technologies is dramatically increasing the use of single nucleotide polymorphisms (SNPs) across the field of genetics, but most parentage studies of wild populations still rely on microsatellites. We developed a bioinformatic pipeline for identifying SNP panels that are informative for parentage analysis from restriction site-associated DNA sequencing (RADseq) data. This pipeline includes options for analysis with or without a reference genome, and provides method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 68 publications
0
67
0
Order By: Relevance
“…This study contributes to a growing body of literature aimed at understanding the power of SNP markers and genotyping‐by‐sequencing methods to assess kinship in wild mammals (Andrews et al, ; Attard et al, ). Further, this is to our knowledge the first study for any mammalian species to investigate how the accuracy and precision of such relatedness estimation affects inference in the analysis of social structure.…”
Section: Introductionmentioning
confidence: 98%
“…This study contributes to a growing body of literature aimed at understanding the power of SNP markers and genotyping‐by‐sequencing methods to assess kinship in wild mammals (Andrews et al, ; Attard et al, ). Further, this is to our knowledge the first study for any mammalian species to investigate how the accuracy and precision of such relatedness estimation affects inference in the analysis of social structure.…”
Section: Introductionmentioning
confidence: 98%
“…Utilizing RADseq for paternity assignment is relatively new (Andrews et al ., ; Thrasher et al ., ). The accuracy of paternity assignment utilizing SNPs has been well documented, especially for the use in livestock and fisheries management (Anderson & Garza, ; Fernandez et al ., ; Hauser et al ., ; Jones et al ., ).…”
Section: Discussionmentioning
confidence: 95%
“…However, in most cases, a reference genome and specific loci have been developed to target specific markers that were previously determined to be variable, making paternity assignment reliable. The mating system for surfperches varies from other taxa evaluated to date because broodsizes are large, yet all offspring are either full siblings (same father) or half siblings (same mother, different father), therefore we report data using the most stringent filtering parameters (following Andrews et al ., ), indicating that all broods were sired by multiple fathers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers new to the field of genomic analyses will still require some time learning entry level bioinformatic skills, but this process is made easier by improved pipelines, such as the stacks software (Catchen, Hohenlohe, Bassham, Amores, & Cresko, ; Paris, Stevens, & Catchen, ), which gets more and more user friendly with each update, as well as documented and user‐friendly scripts for analysis of amplicon sequencing data (Campbell et al, ). Developers continue to improve these pipelines (Andrews et al, ; O'Leary, Puritz, Willis, Hollenbeck, & Portnoy, ; Paris et al, ; Rochette & Catchen, ) and have identified important parameters that should be explored, providing guidance that minimizes the need to test the full parameter space for each new study.…”
Section: Amplicon Sequencing and Sequence Capture Facilitate The Tranmentioning
confidence: 99%